Writing systems, reading processes, and cross-linguistic influences reflections from the Chinese, Japanese and Korean languages - Pae, Hye K. (Bilingual processing and acquisition ;, 2018)
This book provides readers with a unique array of scholarly reflections on the writing systems of Chinese, Japanese, and Korean in relation to reading processes and data-driven interpretations of cross-language transfer. Distinctively broad in scope, topics addressed in this volume include word reading with respect to orthographic, phonological, morphological, and semantic processing as well as cross-linguistic influences on reading in English as a second language or a foreign language. Given that the three focal scripts have unique orthographic features not found in other languages - Chinese as logography, Japanese with multi-scripts, and Korean as non-Roman alphasyllabary - chapters expound script-universal and script-specific reading processes. As a means of scaling up the body of knowledge traditionally focused on Anglocentric reading research, the scientific accounts articulated in this volume importantly expand the field's current theoretical frameworks of word processing to theory building with regard to these three languages.